Article Review: Faktor Risiko dan Klasifikasi Retinopati Diabetik pada Pasien Diabetes Melitus Tipe 2 - Dalillah, Fathian Nur; Yusran, Muhammad; Kurniati, Intanri; Rengganis Wardani, Dyah Wulan Sumekar (Medula, 2024)
Diabetik retinopathy (DR) is a major complication of diabetes mellitus and the leading cause of vision loss. This condition can result in vision impairment and even blindness if not promptly and accurately managed. Risk factors that can increase the likelihood of someone experiencing diabetik retinopathy include age, gender, poor glycemic control, hypertension, dyslipidemia, pregnancy, and smoking. Several of these risk factors can lead to diabetik retinopathy through various mechanisms, such as increased oxidative stress, elevated permeability of retinal blood vessels, formation of hard exudates, and other mechanisms. The classification of diabetik retinopathy is divided into two types: nonproliferative diabetes retinopathy (NPDR) and proliferative diabetes retinopathy (PDR). Nonproliferative is further categorized into three severity levels: mild, moderate, and severe, while proliferative is divided into advanced and very advanced stages. The global prevalence of diabetik retinopathy is approximately 34.6%. In Indonesia, the prevalence of diabetes has reached 10.7 million people, making it one of the top 10 countries with the highest diabetes incidence in the world. The province of Lampung also has a significant number of diabetes cases. According to a study, the prevalence of diabetes in Lampung Province is 9.3%. The objective of this article is to enhance comprehension regarding the risk factors impacting the progression of Diabetic Retinopathy (DR). This piece will explore the factors that contribute to an increased severity of DR.